Validity of the alcohol purchase task: a meta-analysis. - Kiselica, Andrew M.; Webber, Troy A.; Bornovalova, Marina A. (Addiction, 2016)
Background and Aims Behavioral economists assess alcohol consumption as a function of unit price. This method allows construction of demand curves and demand indices, which are thought to provide precise numerical estimates of risk for alcohol problems. One of the more commonly used behavioral economic measures is the Alcohol Purchase Task (APT). Although the APT has shown promise as a measure of risk for alcohol problems, the construct validity and incremental utility of the APT remain unclear. This paper presents a meta-analysis of the APT literature. Methods Sixteen studies were included in the meta-analysis. Studies were gathered via searches of the PsycInfo, PubMed, Web of Science and EconLit research databases. Random-effects meta-analyses with inverse variance weighting were used to calculate summary effect sizes for each demand index-drinking outcome relationship. Moderation of these effects by drinking status (regular versus heavy drinkers) was examined. Additionally, tests of the incremental utility of the APT indices in predicting drinking problems above and beyond measuring alcohol consumption were performed. Results The APT indices were correlated in the expected directions with drinking outcomes, although many effects were small in size. These effects were typically not moderated by the drinking status of the samples. Additionally, the intensity metric demonstrated incremental utility in predicting alcohol use disorder symptoms beyond measuring drinking. Conclusions The Alcohol Purchase Task appears to have good construct validity, but limited incremental utility in estimating risk for alcohol problems.